Electroanalytical Overview: The Electroanalytical Detection of Oxalate - Robert D. Crapnell; Prashanth S. Adarakatti; Craig E. Banks (Sensors and Actuators Reports, 2023)
The sensing of oxalate within urine has been recognised as one of the most important determinations in the investigation of patients with hyperoxaluria. However, current approaches have reported expensive, time consuming, occasionally poor selectivity and are subject to large inaccuracies if great care is not exercised in the handling and measurement of samples. One approach is the use of electroanalytical sensors, which present rapid but highly selective and sensitive outputs, are economical and miniature providing portable sensing platforms to support on-site analysis. In this minireview, recent advances in the electroanalytical sensing of oxalate are presented, overviewing recent electrode configurations and real sample analysis; comparisons to other analytical methods are presented. Finally, the conclusions and future perspective of this field are described in brief.